Socio-demographic determinants of anxiety and depression levels of women after radical surgical treatment for breast cancer - mastectomy - Stępień, Renata B. (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. Socio-demographic determinants of level anxiety and depression of women after radical surgical treatment for breast cancer - mastectomy. Aim. The aim of the research was the assessment of anxiety and depression level in women after radical surgical treatment for breast cancer taking into consideration the impact of socio-demographic factors such as: age, education, marital status, professional activity and place of living. Material and methods. The tested group (n = 217) consisted of patients after radical surgical treatment for breast cancer. The control group consisted of 100 healthy women. The anxiety and depression levels were assessed with Hospital Anxiety and Depression Scale (HADS) by Zigmond i Snaith. Results. The level of anxiety in the patients was 9.58 point, and in the control group - 7.36 (p < 0.001; z = -4.330). The level of depression of the tested group was 6.03 point, and in the control group - 4.95 (p = 0.058; z = -1.894). A pathological level of anxiety was observed in 38,2% (n = 83) patients after mastectomy, and depression in 11.5% (n = 25). Younger patients (under 50) had much lower level of anxiety (p < 0.05; χ 2 = 6.982). Conclusions. 1. Breast cancer and its mutilating surgical treatment negatively affect the emotional condition of the patients, causing significant increase of anxiety. 2. The age (above 50) turned out to be significant predictor of higher anxiety level.